10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background The Certified Nurse Educator (CNE®) credential highlights competency in nursing education and is part of continuing education and professional development for nurse educators. There is limited research on the relationship between CNE certification and teaching, service, and scholarship (TSS). This pilot study explored the relationship of CNE certification and TSS. Method A mixed-methods study survey approach was used with snowball sampling. The total study sample included 213 nursing educators who held the CNE credential, were currently in an academic or clinical teaching role, were at least 18 years old, and taught in the United States. Results Findings suggest that participants perceived connections between CNE certification and all three domains of academic role expectations, with the strongest relationship observed in teaching, followed by service and scholarship. Three subthemes emerged related to teaching: confidence, capability development, and validation of the educator role. Participants described increased comfort in course design, test construction, and student evaluation after CNE certification. Conclusion The pilot study's findings contribute to the limited body of literature examining the role of the CNE credential in academic nursing and suggest that certification may relate to integrated faculty role development. Further research using longitudinal designs and objective measures of TSS outcomes may provide additional insight into how certification relates to sustained professional growth.